PERBANDINGAN DETEKSI Blastocystis hominis DENGAN PEMERIKSAAN MIKROSKOPIS DAN PEMERIKSAAN COPRO ELISA - Muflihatun, Tuti; Bernadus, Janno B. B.; Wahongan, Greta J. P. (Universitas Sam Ratulangi, 2015)
Abstract: Blastocystis hominis is a frequent intestinal protozoa found in human digestive tract that causes Blastocystosis disease. The prevalence of B. hominis was reported in Indonesia about 60%. Blastocystis pose considerable challenges for diagnostic laboratories. Microscopic examination is a